Analisis Kontribusi Sub Sektor Perikanan terhadap Produk Domestik Regional Bruto (PDRB) dan Penyerapan Tenaga Kerja Kabupaten Deli Serdang - GIMTA EIKEL DOANTA; RATNA KOMALA DEWI; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Analysis of The Contribution of Fishery Sub-Sector to Regional GDP and Labor Absorption of Deli Serdang Regency. The potential of fishery and labor resources in Deli Serdang Regency can be developed into a competitive advantage in contributing to regional income. This study aims to determine the contribution of the fishery sub-sector GDP, employment, and the multiplier effect of the fisheries sub-sector on economic and labor growth in Deli Serdang Regency. This quantitative study uses secondary data. The result shows that the contribution of the fishery sub-sector to the regional GDP of Deli Serdang Regency in 2015 to 2019 decreased by 1.27%-1.15%. The contribution of the fishery sub-sector to the workforce in Deli Serdang Regency has been fluctuated. The highest contribution in 2019 was 2.10% and the lowest contribution in 2017 was 1.85%. The multiplier effect of the fishery sub-sector on economic growth based on the regional GDP indicator in Deli Serdang Regency has also fluctuated. Meanwhile, the multiplier effect of the fishery sub-sector on labor growth in Deli Serdang Regency has decreased. The Deli Serdang Regency Government should be able to increase investment and subsidize the price of feed for the fishery sector.